Nutritional and Health Status of Adolescents and their Determinants in the Coastal Areas of Maratua Subdistrict, Berau Regency, East Kalimantan, Indonesia - Anshory, Jamil; Iriyani, Iriyani; Safika, Erri Larene; Wirayanti, Ika Wirya; Kawerang, Andi Tenri; Azhim Ash Siddiq, Muhammad Nuzul; Saputri, Riska Mayang (Journal of Public Health for Tropical and Coastal Region, 2025)
Introduction: Adolescence is a critical period of growth marked by increased nutritional needs and heightened susceptibility to health problems. This study aimed to analyze the nutritional and health status of adolescents and their determinants.Methods: A cross-sectional study was conducted among 47 tenth-grade students at SMAN 9 Berau, recruited through total sampling method. The data collected included anthropometry, blood pressure, hemoglobin levels, and urine tests. Behavioral and psychological factors were assessed using standardized questionnaires: nutrition knowledge, dietary intake (1×24-hour recall and food frequency), Pittsburgh Sleep Quality Index, screen time, and the Depression Anxiety Stress Scale. Data were analyzed descriptively and using chi-square tests.Results: Most adolescents had a normal nutritional status (78%); however, a dual burden of malnutrition persisted, with undernutrition and overweight or obesity affecting over one-fifth of the participants. Dehydration was highly prevalent (89%) and was accompanied by significant cardiometabolic risks, including prehypertension (32%) and chronic energy deficiency risk (38%). Although the overall energy intake was adequate, the insufficient intake of key micronutrients, particularly protein, iron, and folate, remained common. Behavioral and psychosocial vulnerabilities were also prominent, with excessive screen time, poor sleep quality, and notable levels of stress and depression reported by more than half of the respondents. BMI-for-age was significantly associated with blood pressure, chronic energy deficiency risk, and nutritional knowledge (p < 0.05).Conclusion: Despite a predominantly normal nutritional status, adolescents remain at risk of  the double burden of malnutrition, anemia, and micronutrient deficiencies. Strengthening school-based nutrition programs, including regular health screening, practical nutrition education, and improved access to micronutrient support through fortified foods or supplements, is essential for preventing long-term health problems.